A COGNITIVE STYLISTIC ANALYSIS OF SPORTS COMMENTARY - Manar Kareem Mehdi (LP2M UIN Abdul Muthalib Sangadji Ambon, 2025)
Cognitive stylistics always endeavors to scrutinize texts thoroughly to examine the application of theories and concepts in cognitive linguistics to enhance the understanding of texts that condense information in few words. The current research paper sets itself the task of answering the following question: what kind of cognitive stylistic features are implemented in sports commentary and how cognitive stylistic concepts enhance the interpretation of this kind of discourse. As such, the paper aims to identify the cognitive stylistic features implemented in sports commentary by adopting the threefold model of Jeffries and Mclntyre encompassing: schema theory, cognitive metaphor, and contextual frame theory. Accordingly, the study hypothesizes that cognitive metaphors are the most prevalent cognitive stylistic element implemented in sports commentary. The current paper is limited to the analysis of football commentary presented by two commentators who are John Helm and Peter Drury on four World Cup matches. Results of the analysis verify the above mentioned hypothesis.